A new radiological index for the assessment of higher body fat status and lumbar spine degeneration - Özcan-Ekşi, Emel Ece; Kara, Müjdat; Berikol, Gürkan; Orhun, Ömer; Turgut, Veli Umut; Ekşi, Murat Şakir (Skeletal radiology, 2022)
Objective Obesity has been proposed as a risk factor for low back pain (LBP) and intervertebral disc degeneration (IVDD). Even though body mass index (BMI) is used as a parameter for obesity, it could not represent percentage and distribution of the body fat. Subcutaneous fat tissue thickness (SFTT) was proposed as one of the magnetic resonance imaging (MRI) parameters to evaluate the percentage of the body fat. In this study, we aimed to find out whether SFTT at lower back correlated with LBP and spine degeneration. Materials and methods We retrospectively reviewed a database of the patients with LBP. Concomitantly, asymptomatic control subjects were retrieved. Patients and control subjects were evaluated in terms of IVDD and Modic changes at all lumbar levels on MRI. SFTT was measured both on MRI and computed tomography (CT) scans, where applicable. Results SFTT at the lumbar spine had moderate-to-strong correlations with BMI. SFTT at L1-L2 level was significantly associated with severe IVDD at L5-S1 level, and Modic changes at L4-L5 and L5-S1 levels. BMI had no significant association with severe IVDD and Modic changes at lumbar spine. BMI and mean SFTT of all lumbar levels had ORs of 0.735 (95% CI: 0.631–0.857, p < 0.001) and 1.389 (95% CI: 1.266–1.524, p < 0.001) in predicting symptomatic subjects with LBP. Conclusion SFTT at upper lumbar levels could predict severe IVDD and Modic changes better than BMI, specifically in men. SFTT was better than BMI in predicting a symptomatic patient with LBP.